The effects of hypertension on the prognosis of coronavirus disease 2019: a systematic review and meta-analysis on the interactions with age and antihypertensive treatment. Issue 12 (8th December 2022) - Kabia, Alimamy Umaru; Li, Ping; Jin, Zhichao; Tan, Xiaojie; Liu, Yilong; Feng, Yuqi; Yu, Keyao; Hu, Ming; Jiang, Dongming; Cao, Guangwen
Abstract : Background: Hypertension and angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) have been reported to be associated with the prognosis of COVID-19, but the findings remain controversial. Here, we conducted a systematic review to summarize the current evidence. Methods: We retrieved all the studies by MEDLINE via PubMed, CENTRAL, and Embase using the MeSH terms until 30 April 2021. A fixed or random effect model was applied to calculate pooled adjusted odds ratio (AOR) with 95% confidence interval (CI). Interactive analysis was performed to identify the interaction effect of hypertension and age on in-hospital mortality. Results: In total, 86 articles with 18 775 387 COVID-19 patients from 18 countries were included in this study. The pooled analysis showed that the COVID-19 patients with hypertension had increased risks of in-hospital mortality and other adverse outcomes, compared with those without hypertension, with an AOR (95% CI) of 1.36 (1.28–1.45) and 1.32 (1.24–1.41), respectively. The results were mostly repeated in countries with more than three independent studies. Furthermore, the effect of hypertension on in-hospital mortality is more evident in younger and older COVID-19 patients than in 60–69-year-old patients. ACEI/ARBs did not significantly affect the mortality and adverse outcomes of COVID-19 patients, compared with those receiving other antihypertensive treatments. Conclusion: Hypertension is significantly associated with an increased risk of in-hospital mortality and adverse outcomes in COVID-19. The effect of hypertension on in-hospital mortality among consecutive age groups followed a U-shaped curve. ACEI/ARB treatments do not increase in-hospital mortality and other poor outcomes of COVID-19 patients with hypertension.